Buckle-driven delamination models for laminate strength prediction and damage tolerant design. (April 2021) - Köllner, Anton; Nielsen, Mark W.D.; Srisuriyachot, Jiraphant; Rhead, Andrew T.; Butler, Richard
Abstract: Two state-of-the-art analytical compression after impact (CAI) modelling approaches are presented and evaluated for the problem of thin-film buckle-driven propagation of a delamination in composite laminates. Characteristic phenomena are investigated by evaluating the behaviour of the energy release rate of an anisotropic sublaminate above a 2D embedded delamination. These characteristics include extension-bend, shear-bend and bend-twist coupling as well as contact of sublaminate and base laminate. A holistic approach with the aid of a detailed analysis of deformation characteristics from artificial delamination experiments and finite element analysis provide strong validation of the modelling approaches. Suggestions are made regarding analytical methods suitable for use in the initial aerospace structural design stage. It is found that models which capture the mode-mixity and post-buckled energy terms accurately will allow for better design decisions to be made that are not overly conservative. Whereas methods, which do not account for such mixity and post-buckling, can nevertheless be used to design for damage tolerance. Highlights: Analytical, numerical and experimental investigation of buckle-driven delamination propagation in composite laminates. Two state-of-the-art analytical approaches presented aiming at damage tolerant design for compression-after-impact (CAI) strength. Detailed experimental study using DIC analysis and ultrasonic C-scans. Insight into the effect of anisotropy, post-buckling deformation and stiffness, and contact.